A Review on Synthetic Approaches and Applications of Starch Nanomaterials, and Hydrolyzed, Esterified and Phosphorylated Starch Materials (OODBODHAN, 2025)
Starch undergoes chemical modification through functionalization, and it naturally exists in numerous nano-sized semi crystalline block lets. From starch, low toxicity and eco-friendly compounds with high modification can be prepared for commercial applications. So, it is an interesting and advantageous bioactive polymer in the field of nanotechnology. The quality change in functionality of starch can be seen by the substitution of a new functional group in the starch molecule. Chemical modifications through the processes of hydrolysis, esterification, and phosphorylation have been reported to result in the starch functionalized derivatives of specific applications mainly in agricultural, food and non-food industries, water treatment, drug delivery and paper and textile industries. Varieties of nanomaterials can be extracted from starch for many purposes like fat mimic, delivery system, emulsion stabilizing and food packaging, DNA precipitation and cancer therapy.